Urbanicity Gradients Are Associated with the Household- and Individual-Level Double Burden of Malnutrition in Sub-Saharan Africa. Issue 6 (11th May 2016) - Jones, Andrew D; Acharya, Yubraj; Galway, Lindsay P
Abstract: Background : The nutrition transition is advancing throughout sub-Saharan Africa (SSA). However, the nutritional risk across urbanicity gradients associated with this transition is not clear. Objectives: We aimed to determine 1 ) the extent to which overweight and anemia in women of childbearing age (WCBA) and stunting in preschool-age children (PSC) are spatially correlated within countries of SSA; and 2 ) the association of urbanicity with the individual-level nutritional double burden (i.e., concurrent overweight and anemia within an individual WCBA), the household-level double burden (i.e., overweight WCBA and stunted PSC in the same household), and the 3 components of these double burdens (i.e., overweight, anemia, and stunting). Methods: We used Demographic and Health Surveys (DHS) data for 30 countries in SSA from 2006–2012. We calculated overweight [body mass index (BMI; in kg/m 2 ) ≥25] and anemia (hemoglobin concentration <120 g/L) in WCBA, and stunting in PSC aged 12–59 mo (height-for-age z score <−2). We used population density, measured using a high-resolution population distribution dataset, to define gradients of urbanicity. We used geolocated DHS data to calculate cluster-level mean population densities and the Moran's I statistic to assess spatial autocorrelation. Results: Cluster-level BMI values and hemoglobin concentrations for WCBA were spatially correlated. The odds of overweight in WCBA were higher in periurban and urban areas than in rural areas (periurban, OR: 1.08; 95% CI: 1.01, 1.16; urban, OR: 1.26; 95% CI: 1.18, 1.36), as were the odds of stunting in PSC in periurban areas (OR: 1.13; 95% CI: 1.06, 1.22). The odds of both double burden conditions were higher in periurban and urban areas than in rural areas (individual-level—periurban, OR: 1.18; 95% CI: 1.05, 1.33; urban, OR: 1.43; 95% CI: 1.27, 1.61; household-level—periurban, OR: 1.24; 95% CI: 1.06, 1.44; urban, OR: 1.24; 95% CI: 1.06, 1.46). Conclusion: Urban and periurban areas in SSA may be particularly vulnerable to the nutritional double burden compared with rural areas. Clearly differentiating urban environments is important for assessing changing patterns of nutritional risk associated with the nutrition transition in SSA.